2014
DOI: 10.1016/j.rasd.2014.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Visual search strategies during facial recognition in children with ASD

Abstract: Facial recognition is a complex skill necessary for successful human interpersonal and social interactions. Given that the most prevalent disorder of social interaction is autism spectrum disorder (ASD), a number of studies have investigated and found impaired facial recognition abilities in people with ASD. Further, this impairment may be critically involved in mediating the deficits in interpersonal and social interactions in people with ASD. We sought to address the question of whether face processing is im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…This strategy may be more flexible or underdeveloped in childhood and only impact performance once it is established in adulthood. Studies examining face perception with eye-tracking methods have found that children and adults with ASD use atypical local and global strategies (e.g., Albrecht et al, 2014;Falkmer, Larsson, Bjällmark, & Falkmer, 2010). Specifically, compared to TD children, some studies have shown that children with ASD fixate more on individual features, such as the eyes and mouths, but show no differences in recognition accuracy (Albrecht et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This strategy may be more flexible or underdeveloped in childhood and only impact performance once it is established in adulthood. Studies examining face perception with eye-tracking methods have found that children and adults with ASD use atypical local and global strategies (e.g., Albrecht et al, 2014;Falkmer, Larsson, Bjällmark, & Falkmer, 2010). Specifically, compared to TD children, some studies have shown that children with ASD fixate more on individual features, such as the eyes and mouths, but show no differences in recognition accuracy (Albrecht et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining face perception with eye-tracking methods have found that children and adults with ASD use atypical local and global strategies (e.g., Albrecht et al, 2014;Falkmer, Larsson, Bjällmark, & Falkmer, 2010). Specifically, compared to TD children, some studies have shown that children with ASD fixate more on individual features, such as the eyes and mouths, but show no differences in recognition accuracy (Albrecht et al, 2014). In contrast, others have demonstrated that adults with ASD fixate more on irrelevant facial features than eyes and perform poorer than neurotypical adults (Falkmer et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A large number of strategies used in educational intervention for students with ASD are based on transferring information using visual aids and materials. There is research to support that these students have a tendency towards visual and structured thinking (Lissner, 1992;Gray, 1998;Savner & Smith Myles, 2000;Albrecht, et al 2014). Later works of Grandin (2009) state that visual supports can have an indirect as well as a direct impact on social skills.…”
Section: Introductionmentioning
confidence: 99%